A Comparative Study of Cultural Types and Dimensions in English Textbooks - Kristina Butar Butar; Arsen Nahum Pasaribu (Pusat Studi Pendidikan Bahasa dan Sastra Inggris, 2021)
Many researchers have conducted regarding cultural analysis in English textbooks. However, the comparison between English Textbook as ESL and EFL used in Indonesia in term of cultural analysis is relatively unexplored. After addressing the gap, this study mainly focuses on investigating the cultural contents between Cambridge Global English Key Stage 6 and Erlangga Grow with English Book. The data of the study were taken from the two books regarding the cultural dimensions. The theory of types of culture used is proposed by Hinkel (1999), namely source, target, and international culture. As for the theory of dimensions of culture, namely aesthetic, sociological, semantic, and pragmatic is taken from Adaskou, Britten and Fahsi. The findings reveal that Cambridge Global English Key Stage 6 contained more cultural materials than Erlangga Grow with English Book 6. Cambridge Global English Key Stage 6 contains more percentage or portion in culture types and dimensions which considers the importance of studying culture as a preparation for the learners to face intercultural communication in their future. This study contributes to a new perspective in the study of cultural dimension as well as a new horizon in a comparative study in ELT.